2020
DOI: 10.1021/acs.jcim.0c00491
|View full text |Cite
|
Sign up to set email alerts
|

Computational Determination of Potential Inhibitors of SARS-CoV-2 Main Protease

Abstract: The novel coronavirus (SARS-CoV-2) has infected several million people and caused thousands of deaths worldwide since December 2019. As the disease is spreading rapidly all over the world, it is urgent to find effective drugs to treat the virus. The main protease (Mpro) of SARS-CoV-2 is one of the potential drug targets. Therefore, in this context, we used rigorous computational methods, including molecular docking, fast pulling of ligand (FPL), and free energy perturbation (FEP), to investigate potential inhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
186
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(193 citation statements)
references
References 63 publications
5
186
0
Order By: Relevance
“…Currently, scientific community are largely focused in the screening of – (i) FDA-approved drug databases, (ii) clinical trials molecules and/or (iii) previously reported coronavirus inhibitors 9 . In silico virtual screening (VS) techniques are proficient to explore CoV protease inhibitors 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 . Yu and co-workers 40 reported the computational screening and findings with regard to potential binding luteolin and other natural compounds against Mpro.…”
Section: Search Of Protease Inhibitors Against Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, scientific community are largely focused in the screening of – (i) FDA-approved drug databases, (ii) clinical trials molecules and/or (iii) previously reported coronavirus inhibitors 9 . In silico virtual screening (VS) techniques are proficient to explore CoV protease inhibitors 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 . Yu and co-workers 40 reported the computational screening and findings with regard to potential binding luteolin and other natural compounds against Mpro.…”
Section: Search Of Protease Inhibitors Against Covid-19mentioning
confidence: 99%
“…Vast amount of in silico VS studies against SARS-CoV-2 Mpro has been reported over past months 26-30, 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 . As the detailed description on the molecular modeling studies is out of Scope for this current communication, readers interested in learning more about recent molecular modeling studies to identify probable CoV protease inhibitors are directed to mentioned references 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72...…”
Section: Search Of Protease Inhibitors Against Covid-19mentioning
confidence: 99%
“… 240 In this case, ritonavir, lopinavir, and darunavir (anti-HIV drugs) were considered, and it was finally suggested that darunavir should be more selective for recognizing PLpro instead of 3CLpro. Nevertheless, additional docking studies suggest that darunavir could also be a suitable choice to bind 3CLpro, 241 , 242 highlighting the relevance of this particular anti-HIV drug as a potential anti-COVID-19 clinical drug.…”
Section: Sars-cov-2 Proteasesmentioning
confidence: 99%
“…Furthermore, it has been recently reported that nelfinavir had anti-SARS-CoV-2 activity, as demonstrated in a cell-based experimental assay [12,13]. In addition, other HIV protease inhibitors such as indinavir, darunavir, and saquinavir, have been proposed as drug candidates against SARS-CoV-2 M pro , using computational studies [14][15][16][17][18]. These HIV protease inhibitors are repurposed drug candidates, some of which are already being tested in clinical trials.…”
Section: Introductionmentioning
confidence: 99%